Percutaneous endoscopic lumbar discectomy compared with other surgeries for lumbar disc herniation: A meta-analysis. Issue 9 (5th March 2021) - Bai, Xiaoliang; Lian, Yong; Wang, Jie; Zhang, Hongxin; Jiang, Meichao; Zhang, Hao; Pei, Bo; Hu, Changqing; Yang, Qiang
Abstract: Objective: This meta-analysis was performed to investigate whether percutaneous endoscopic lumbar discectomy (PELD) had a superior effect than other surgeries in the treatment of patients with lumbar disc herniation (LDH). Method: We searched PubMed, Embase, and Web of Science through February 2018 to identify eligible studies that compared the effects and complications between PELD and other surgical interventions in LDH. The outcomes included success rate, recurrence rate, complication rate, operation time, hospital stay, blood loss, visual analog scale (VAS) score for back pain and leg pain, 12-item Short Form Health Survey (SF12) physical component score, mental component score, Japanese Orthopaedic Association Score, Oswestry Disability Index. A random-effects or fixed-effects model was used to pool the estimate, according to the heterogeneity among the included studies. Results: Fourteen studies (involving 2, 528 patients) were included in this meta-analysis. Compared with other surgeries, PELD had favorable clinical outcomes for LDH, including shorter operation time (weight mean difference, WMD=−18.14 minutes, 95%CI: −25.24, −11.05; P  < .001) and hospital stay (WMD = −2.59 days, 95%CI: −3.87, −1.31; P  < .001), less blood loss (WMD = −30.14 ml, 95%CI: −43.16, −17.13; P  < .001), and improved SF12- mental component score (WMD = 2.28, 95%CI: 0.50, 4.06; P  = .012)) and SF12- physical component score (WMD = 1.04, 95%CI: 0.37, 1.71; P  = .02). However, it also was associated with a significantly higher rate of recurrent disc herniation (relative risk [RR] = 1.65, 95%CI: 1.08, 2.52; P  = .021). There were no significant differences between the PELD group and other surgical group in terms of success rate (RR = 1.01, 95%CI: 0.97, 1.04; P  = .733), complication rate (RR = 0.86, 95%CI: 0.63, 1.18; P  = .361), Japanese Orthopaedic Association Score score (WMD = 0.19, 95%CI: −1.90, 2.27; P  = .861), visual analog scale score for back pain (WMD = −0.17, 95%CI: −0.55, 0.21; P  = .384) and leg pain (WMD = 0.00, 95%CI: −0.10, 0.10; P  = .991), and Oswestry Disability Index score (WMD = −0.29, 95%CI: −1.00, 0.43; P  = .434). Conclusion: PELD was associated with better effects and similar complications with other surgeries in LDH. However, it also resulted in a higher recurrence rate. Considering the potential limitations in the present study, further large-scale, well-performed randomized trials are needed to verify our findings.